THE LATIHAN SKIPPING DENGAN TEKNIK HIGH STEP MENINGKATKAN TINGGI LONCATAN PEMAIN BOLA BASKET - Novianti, I.G.A Sri Wahyuni; Winaya, I Made Niko; Tianing, Ni Wayan (Majalah Ilmiah Fisioterapi Indonesia; Vol 3 No 2 (2015): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2015.v03.i02.p08)
This study aims to determine the skipping exercise with high step technique to increase men basketball player vertical jump in junior high school 1 Denpasar. This research method is pre–experimental which used one group pre-test and post-test group design conducted in May to June 2014 where the population of this study was students in junior high school 1 Denpasar who follow the basketball extracurricular , they were at the age of 12–15 (mean 13.2±0.616) years old. Sampling technique in this study is purposive sampling with a sample of 20 people. The sample joined to do skipping exercise with high step technique for 4 weeks which was 3 times a week. The results the of study by using the paired sample t-test showed that the mean increase in vertical jump before and after exercise showed p=0.000 (p <0.05) mean difference 7.25±1.06. The conclusion is skipping exercise with high step technique significantly increase the vertical jump among basketball player by 1.97%.
Keywords: skipping with high step technique,vertical jump, basketball